'My heart inclines wholly to know where is the true good': Mia Hansen-Løve's Postsecular Search for God. Issue 3 (November 2019) - Wheatley, Catherine
Abstract : This article explores how Mia Hansen-Løve's cinema thinks about the experience of a life in which God is absent, and yet his ghost continues to haunt us. It suggests links between her films and postsecular theory, especially deconstructions of religion by Jean-Luc Nancy and Jacques Derrida. Although Hansen-Løve's films are not 'about' religion in any meaningful sense of the word, religious imagery and theological allusions abound. Her cinema also displays a consistent thematic concern with vocation. The secularized vocations that Hansen-Løve's characters pursue remain bound to and by their religious roots, as well as coming to serve as a substitute for religious calling.